(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
This paper analyzes global threats in the world economy and their impact on economic development, taking the COVID-19 pandemic as a case study. The increasing interconnections of economic systems in the context of globalization has facilitated the rapid and widespread spread of global risks. The study examines the effects of the pandemic on production volumes, international trade, employment levels, and GDP indicators. Based on statistical data and analytical approaches, the COVID-19 pandemic has caused a short-term decline in the global economy, increased financial instability, and strained government budgets. At the same time, it has accelerated the development of the digital economy, remote work, and e-commerce. The findings highlight the need to strengthen economic stability mechanisms and develop strategies to mitigate the impact of future global threats.